Qat Chewing as an Independent Risk Factor for Periodontitis: A Cross-Sectional Study - Ali Kaid Al-Sharabi; Hussien Shuga-Aldin; Ibrahim Ghandour; Nezar Noor Al-Hebshi (International Journal of Dentistry)
This study assessed the effect of qat chewing on periodontal health, independent of other risk factors. Four hundred qat chewers and 100 nonchewers (20–50 years) were included. Demographic data and detailed information about chewing and smoking were obtained. Periodontal status was assessed using Community Periodontal Index (CPI) and clinical attachment loss (CAL). The qat chewers were older, included more males and smokers, and had worse oral hygiene but higher education levels; the majority were heavy chewers (mean duration of 14.45 years and frequency of 6.10 days/week). Regression analysis identified age, oral hygiene, education level, and cigarette smoking as independent predictors of periodontal destruction. Adjusted for these, qat chewing showed marginally significant association only with CAL (OR = 4.7; P=0.049). The chewing sides showed significantly higher scores than the nonchewing sides; however, equal scores on both sides or lower scores on the chewing sides (possibly no or beneficial effect) were still observed in 50% of the chewers. Heavy qat chewing is shown here as an independent risk factor for attachment loss. However, the possibility that the habit may have beneficial effects in a subset of the chewers cannot be excluded. A holistic model that resolves the existing contradiction is presented.